Human adaptation to mid- to late-Holocene climate change in Northeast Thailand. (November 2016) - Wohlfarth, Barbara; Higham, Charles; Yamoah, Kweku Afrifa; Chabangborn, Akkaneewut; Chawchai, Sakonvan; Smittenberg, Rienk H
This article integrates palaeoenvironmental and archaeological sequences covering the mid- to late-Holocene in Northeast Thailand. The former reveal the fluctuating intensity of the Asian summer monsoon, leading to periods of higher moisture availability with intervals of relative aridity. The latter are founded on a series of new radiocarbon determinations that provide a basic chronological framework, from the initial Neolithic settlements by rice farmers (c. 3700 cal. BP) to the end of the prehistoric Iron Age around 1300 cal. BP. By dovetailing the two, we find that periods of relative aridity occurred during the later Iron Age as an agricultural revolution witnessed water control measures, plough and irrigated rice cultivation and a marked rise in social elites. The correlation between climatic and cultural changes is found to continue into the period of the Angkorian state. Rather than cause a decline and/or abandonment of late Iron Age settlements, we find that the environmental stress caused by a weaker summer monsoon was met by a strong social response and by adaptations that generated a transition into early socially hierarchic polities.